Arte contemporânea digital amazônica no Museu de Arte Xumucuís: plataforma virtual para preservação e exibição - Deyse Ane Ribeiro Marinho (2024)
This dissertation aims to present the experience of the Xumucuís Art Museum platform for the preservation and exhibition of Amazonian digital contemporary art. In the first chapter, I delve into the history of the Xumucuís project since 2010, culminating in the establishment of the museum in 2021. The second chapter includes an analysis of its collection of works, cataloging, as well as references to documentation and preservation of digital art. The third chapter concludes by introducing guidelines and procedures for the incorporation of the work "Ahora" (2007-2010), a multimedia installation by the Paraense artist Melissa Barbery, in a case study focusing on the work and its preservation for future exhibitions.